2011
DOI: 10.1210/jc.2010-2729
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Monitoring of Circadian Glycemic Patterns In Patients Receiving Prednisolone For COPD

Abstract: Prednisolone predominantly causes hyperglycemia in the afternoon and evening. Treatment of prednisolone-induced hyperglycemia should be targeted at this time period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
103
2
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 21 publications
17
103
2
7
Order By: Relevance
“…The latter two reports showed FPG was not increased by glucocorticoids. The different points of Rizza's study from the latter two reports are 1) Study subjects were healthy volunteers, and 2) Glucocorticoid treatment period was much shorter (24-h infusion) in healthy volunteers than in patients with chronic obstructive pulmonary disease or Cushing's syndrome [3,13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter two reports showed FPG was not increased by glucocorticoids. The different points of Rizza's study from the latter two reports are 1) Study subjects were healthy volunteers, and 2) Glucocorticoid treatment period was much shorter (24-h infusion) in healthy volunteers than in patients with chronic obstructive pulmonary disease or Cushing's syndrome [3,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Rizza et al showed that cortisol increased fasting glucose production and more insulin was required to reduce glucose production after cortisol infusion than saline by euglycemic hyperinsulinemic clamp studies on healthy volunteers [13]. On the other hand, synthetic glucocorticoids particularly increase postprandial PG, but not FPG, in patients with chronic obstructive pulmonary disease [14]. It has been reported that endogenous glucocorticoid excess in patients with Cushing's syndrome predominantly increases postprandial PG with FPG often in the normal range [3].…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown what contribution this hypersensitive state may have had in exacerbating or predisposing to glucose intolerance following even a single prednisone dose. Furthermore, it has been reported that interstitial hyperglycaemia associated with prednisolone treatment is predominantly manifested in the afternoon and evening in patients receiving prednisolone treatment while undergoing continuous glucose monitoring (31). Accordingly, the OGTT was conducted during the mid-late afternoon.…”
Section: Discussionmentioning
confidence: 99%
“…The role of b 2 -agonists and oral steroid therapy has already been demonstrated [132]. SUISSA et al [133] confirmed that high-dose inhaled corticosteroids are a risk factor for the development or poor control of diabetes.…”
Section: Impact Of Treatmentsmentioning
confidence: 96%